Islamic Finance, Ownership Risk and Right to Yield: Gaps in Theory and Practice - Mohammad Abdullah (Türkiye İslam İktisadı Dergisi)
From a shariah perspective, the rights and obligations of parties in exchange contracts are determined based on the different underlying contractual structures. Among the key shariah principles that provide conceptual premises for determination of yield-entitlement from an investment, include the principles of al-kharaj bil-dhaman and al-ghunm bil-ghurm. According to these two principles, in order to be entitled to a financial return or yield, the owner of an underlying asset, activity or capital must bear the related market as well as ownership risks. These two principles have a great bearing on how the shariah-compliant banking and financial activities are conducted. In the context of Islamic Financial Institutions (IFIs), the requirement of dhaman exposes IFIs to a new form of risk i.e., ownership risk. To this effect, IFIs in different capacities need to assume ownership-risk to justifiably claim a financial return from a financing activity. Notwithstanding this, in the customary practices of IFIs, there are noted discrepancies in the application of the dhaman principle. The objective of this paper is to examine the application of the dhaman principle in different contractual structures of IFIs, followed by highlighting the existing gaps between the theory and practice in applying this concept. The research adopts a qualitative research approach in order to examine the issue. The paper is based on a review of relevant literature and adopts a textual analysis method. The paper argues that if there is a discrepancy in application of dhaman principle, the shariah status of the resulting yield may be affected. Among the key implications of such a discrepant application of dhaman concept include allocation of yield to a non-deserving party; the party which practically shifts the underlying dhaman of the relevant contract rather than absorbing it. As a policy recommendation, the paper suggests strategies to re-align the practice of Islamic banking with its theories, particularly, with reference to directing the relevant risk to the one who claims the yield.